Legitimacy of using force to keep peace : implications of the blue helmets' perceptions for the success of robust peacekeeping operations - Goulart, Fernando Rodrigues (2022)
Tese (doutorado) — Universidade de Brasília, Instituto de Relações Internacionais, Programa de Pós-Graduação em Relações Internacionais, 2022.